Economic Analysis, Effectiveness And Efficiency Of Budget Use In Infrastructure Projects - Sholeha; Rahma, Filasti; Saputri, Andriani (International Journal of Multidisciplinary Learners, 2025)
Regional government financial measurements are carried out by accommodating the results that have been achieved during a period with the previous period, namely what financial trends have occurred. Several ratios used to reduce regional government financial performance based on financial data available in the APBD include economic, effectiveness and efficiency ratios. This research aims to analyze and measure the economy, effectiveness and efficiency of budget use in infrastructure projects. The population in this research is budget realization reports. The sampling technique used in this research is the 2018-2022 Budget Realization Report. The research method is a quantitative descriptive type that uses primary data and secondary data. The data collection techniques used in this research are documentation and interview techniques. The data analysis technique uses ratio analysis. The results of the research show that the percentage of economic ratios in budget use is in the very economical category, while based on the effectiveness ratio in budget use it is in the quite effective criteria, and based on the efficiency ratio in budget use it is in the very efficient category.